Effect of Improved Production Systems on Productivity of Local Chickens in Rural Areas of Babati District, Tanzania - International Livestock Research Institute (International Food Policy Research Institute, 2019)
Local chickens in rural areas are mostly kept under minimal input of resources though they contribute significantly to food security, poverty alleviation and ecologically sound management of natural resources. The free-range system is predominant, whilst a few households have adopted a semi-intensive system or intensive system. Under scavenging and semi-intensive systems, chickens are rarely fed more than kitchen leftovers, although occasionally they are supplemented with grains or their by-products. Given the low number of chickens, farmers do not find it economical to construct a separate house for their chickens and in most cases, chickens spend the night time in the human dwelling. Periodic disease outbreaks resulting from inadequate biosecurity measures and poor feeding which consequently leads to low growth rate and low egg production with high mortality rates. Losses are mostly observed in young chicks and growers. The Africa RISING projects introduced technologies to assess simple and low cost-effective technologies of improved supplementation and housing for increased performance of local chickens in rural areas of Babati district. The technologies were: - Improved feed rations (compounded) using vegetable wastes and other locally available grains and by-products as feed components; - Improved poultry housing for full or partial confinement of chicken; The current data reflects the effect of the introduced technologies on growth, egg production and mortality rate of local chickens.